2014
DOI: 10.4161/mabs.29978
|View full text |Cite
|
Sign up to set email alerts
|

Interference of HCV replication by cell penetrable human monoclonal scFv specific to NS5B polymerase

Abstract: dodecyl sulfate; SOC, standard-of-care; STAT-C, specifically targeted anti-viral therapy for hepatitis C; SVR, sustained virologic response; VH, variable heavy chain domain of conventional four-chain IgG; V H H, variable heavy chain domain of heavy chain antibody; VL, variable light chain domainA new class of hepatitis C virus (HCV)-targeted therapeutics that is safe, broadly effective and can cope with virus mutations is needed. The HCV's NS5B is highly conserved and different from human protein, and thus it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 42 publications
(87 reference statements)
0
34
0
Order By: Relevance
“…CPPs provide an ideal means for intracellular delivery of the growing number of pharmaceutically relevant proteins. Previous studies reported that nanobodies fused with CPPs could pass through the cell membrane and interfere with hepatitis C virus replication (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…CPPs provide an ideal means for intracellular delivery of the growing number of pharmaceutically relevant proteins. Previous studies reported that nanobodies fused with CPPs could pass through the cell membrane and interfere with hepatitis C virus replication (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Cell penetrating ability of the PEN-nanobodies was determined by indirect ELISA and confocal microscopy as described previously [ 26 , 27 ]. The Huh7 cells were cultured in DMEM supplemented with 10% heat inactivated fetal calf serum (Hyclone, South Logan, TX, USA), penicillin (50 units/mL) and streptomycin (50 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…CytoTox96® non-radioactive cytotoxicity (lactate dehydrogenase, LDH) assay kit (Promega, Madison, WI, USA) was used for determining toxicity of the HCV protease specific-transbodies [ 25 , 26 , 27 ]. The Huh7 cells were cultured as above; 2 × 10 4 cells were added to individual wells of a 96 well tissue culture plate and incubated at 5% CO 2 incubator at 37 °C for 24 h. The monolayer were washed twice with PBS before incubating with 25 µg PEN-V H Hs for 24 h. Cells incubated with medium alone and 10% SDS were included as negative and positive cytotoxic controls, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations